Utilization of Land Pawning Objects in Minangkabau in The Perspective of The Scholars of Schools of Thought - Hayati, Ilda; Djamil, Fathurrrahman; Edyar, Busman (Institut Agama Islam Negeri Curup, 2022)
This paper aims to explain the practice of pawning in Sariek Laweh, the law on the use of land pawning objects in Minangkabau from the perspective of Islamic scholars, and the solutions of pawning. This research is a field study using a normative approach, which is analyzed using a comparative descriptive method. The results of the study are: that in general, pawning in Minangkabau is carried out with the ability to use the object of land pawning and to take all the proceeds by the pawn holder. This applies until the mortgagee is able to pay off the debt. Scholars have different opinions regarding the use of pawn objects by pawn holders, the majority (jumhur ulama) forbid it. The second opinion (minority) says that it is permissible to take advantage of the pawn object, but there are still provisions in this matter. Based on the findings of this study, the practice of pawning in Sariek Laweh is not in accordance with the provisions of the Islamic Sharia which are seen from various schools of thought, apart from the element of exploitation of the pawn holder, the mortgagee does not receive any compensation from the goods used, other than fixed loan funds which must be paid according to the amount of the initial loan, without any reduction, also because there are conditions for taking benefits included in the contract, all schools of thought agree that this practice is not permissible. Regarding the pawning solution, it is in the form of musyarakah between the pawn holder and the owner of the pawn object. The pawn holder processes and takes the proceeds with a sharing system with the land owner.